Pengaruh Indeks Pembangunan Manusia (IPM) dan Pengangguran terhadap Pertumbuhan Ekonomi di Kota Banjarmasin - Sayidah Fitri Alkhoiriyah; Chairul Sa’roni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study aims to determine and analyze the effect of the Human Development Index (HDI) and unemploymenton Economic Growth in the City of Banjarmasin. This type of research is quantitative research with secondary data. While the location of research is in the city of Banjarmasin, the data used in this study arethe Human Development Index (HDI) and unpleyment data in Banjarmasin City for 11 years in the 2009-2019 period. The data that has beendata obtained is then analyzed by analyzing multiple linear regression equations with the help og the SPSS software program version 26.0.The research results in a partial analysis of the Human Development Index (HDI) signifanctly influence economic growth in the city of Banjarmasin. Unemployment is partially negative and significant effect on economic growt in the city of Banjarmasin and simultaneously the Human Development Index (HDI) and unemployment have a significant effect on economic growth in the city of Banjarmasin during 2009-2019.